Minimally invasive discectomy versus open laminectomy and discectomy for the treatment of cauda equina syndrome: A preliminary study and case series - Khashan, Morsi; Ofir, Dror; Grundshtein, Alon; Kuzmenko, Boris; Salame, Khalil; Niry, Dana; Hochberg, Uri; Lidar, Zvi; Regev, Gilad J. (Frontiers in Surgery, 2022)
Background: Cauda Equina syndrome (CES) is a potentially devastating condition and is treated usually with urgent open surgical decompression of the spinal canal. Currently, the role of minimally invasive discectomy (MID) as an alternative surgical technique for CES is unclear . Objective: The purpose of this study was to compare clinical outcomes following MID and open laminectomy and discectomy for the treatment of CES. Methods: The study cohort included patients that underwent surgery due to CES at our institute. Patients’ outcomes included: surgical complications, length of hospitalization, postoperative lower extremity motor score (LEMS), Numerical Rating Scale (NRS) for leg and back pain, Oswestry disability index (ODI), and the EQ-5D health-related quality of life questionnaire. Results: Twelve patients underwent MID and 12 underwent open laminectomy and discectomy. Complications and revisions rates were comparable between the groups. Postoperative urine incontinence and saddle dysesthesia improved in 50% of patients in both groups. LEMS improved from 47.08 ± 5.4 to 49.27 ± 0.9 in the MID group and from 44.46 ± 5.9 to 49.0 ± 1.4 in the open group. Although, leg pain improved in both groups from 8.4 ± 2.4 to 3±2.1 in the MID and from 8.44 ± 3.3 to 3.88 ± 3 in the open group, significant improvement in back pain was found only in the MID group. Final functional scores were similar between groups. Conclusions: Our preliminary results suggest that minimally invasive discectomy is an effective and safe procedure for the treatment of CES when compared to open laminectomy and discectomy. However, MID in these cases should only be considered by surgeons experienced in minimally invasive spine surgery. Further studies with bigger sample sizes and long-term follow-ups are needed.